Analisa Kebijakan Pemerintah Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi pada DKI Jakarta - Leonard , Leonard; Eric Lionel; Toni Ong; Nico Fernando; Vikhri septama (Universitas Maritim AMNI Semarang, 2022)
Unemployed are people or people who have not got a job, are looking for work and have lost their job or are not working at all. This study aims to analyze Government Policy Related to the Threat of Unemployment Post-Inflation Increase in DKI Jakarta. The research method used in this research is by using quantitative methods. The object of analysis will be obtained from BPS or the Central Statistics Agency. BPS is an institution that deals with censuses and statistics. The results show that the numbers can affect a state's income because not having income can cause economic problems and poverty. Therefore, government policies are urgently needed to overcome this unemployment.